Ultra wideband systems with MIMO - Kaiser, Thomas, Prof. Dr.-Ing (Wiley, 2010)
Up-to-date coverage of the cutting-edge research on UWB Systems with Multiple Antennas. In this book, the authors investigate the benefits of combining UWB and MIMO technologies; highlighting five aspects of this promising research field: channel capacity, space-time coding, beamforming and localization, time-reversal transmission, and UWB-MIMO relay. The book presents a systematic and in-depth discussion for each of the hot topics, providing an insight into the cutting-edge research currently undertaken. It is expected that the ideas and approaches illustrated in this book will inspire sparks.